Drivers of Variability in 90-Day Cost for Elective Anterior Cervical Discectomy and Fusion for Cervical Degenerative Disease. Issue 5 (1st May 2018) - Chotai, Silky; Sivaganesan, Ahilan; Parker, Scott L; Sielatycki, John A; McGirt, Matthew J; Devin, Clinton J
Abstract: BACKGROUND: Value-based episode of care reimbursement models is being investigated to curb unsustainable health care costs. Any variation in the cost of index spine surgery can affect the payment bundling during the 90-d global period. OBJECTIVE: To determine the drivers of variability in cost for patients undergoing elective anterior cervical discectomy and fusion (ACDF) for degenerative cervical spine disease. METHODS: Four hundred forty-five patients undergoing elective ACDF for cervical spine degenerative diagnoses were included in the study. The direct 90-d cost was derived as sum of cost of surgery, cost associated with postdischarge utilization. Multiple variable linear regression models were built for total 90-d cost. RESULTS: The mean 90-d direct cost was $17685 ± $5731. In a multiple variable linear regression model, the length of surgery, number of levels involved, length of hospital stay, preoperative history of anticoagulation medication, health-care resource utilization including number of imaging, any complications and readmission encounter were the significant contributor to the 90-d cost. The model performance as measured by R2 was 0.616. CONCLUSION: There was considerable variation in total 90-d cost for elective ACDF surgery. Our model can explain about 62% of these variations in 90-d cost. The episode of care reimbursement models needs to take into account these variations and be inclusive of the factors that drive the variation in cost to develop a sustainable payment model. The generalized applicability should take in to account the differences in patient population, surgeons' and institution-specific differences.